2017
DOI: 10.1177/1687814017724704
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing tool size and tool path of five-axis flank milling with bounded constraints via normal mapping

Abstract: This article presents an approach to generate optimal couples of tool size and tool path for flank milling ruled surface with a conical cutter based on normal mapping, while at the same time keeping this couples within the given bounded constraints. For given initial pairs of taper tool and tool path, tool envelope surface is calculated. Then, the tool axis trajectory surface is related to envelope surface through the normal mapping. On this basis, the correspondence between the surface pair ''design ruled sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Optimizing simultaneously both the tool trajectory and its size and/or shape is a very active research area [25,26,27,28,29,30] and our research belongs to this category of algorithms. To the best of our knowledge, all previous research requires the initial milling trajectory as a part of the input or is indicated by the user.…”
Section: Previous Work and Contributionsmentioning
confidence: 99%
“…Optimizing simultaneously both the tool trajectory and its size and/or shape is a very active research area [25,26,27,28,29,30] and our research belongs to this category of algorithms. To the best of our knowledge, all previous research requires the initial milling trajectory as a part of the input or is indicated by the user.…”
Section: Previous Work and Contributionsmentioning
confidence: 99%
“…The most recent research focuses on custom-shaped tools. That is, not only the 3D motion of the tool, but also the shape itself are the unknowns in path-planning [19,51,52,53,54,55]. Typically, the initial milling trajectory is a part of the input or is indicated by the user.…”
Section: Cnc Machiningmentioning
confidence: 99%
“…The most recent research focuses on custom-shaped tools. That is, not only the 3D motion of the tool, but also the shape itself are the unknowns in path-planning [19,51,52,53,54,55]. Typically, the initial milling trajectory is a part of the input or is indicated by the user.…”
Section: Previous Workmentioning
confidence: 99%